Should We Assess Pituitary Function in Children After a Mild Traumatic Brain Injury? A Prospective Study - Briet, Claire; Braun, Karine; Lefranc, Michel; Toussaint, Patrick; Boudailliez, Bernard; Bony, Hélène (Frontiers in Endocrinology, 2019)
Objective: The aim of this study was to evaluate the frequency of hypopituitarism following TBI in a cohort of children hospitalized for mild TBI and to identify the predictive factors for this deficiency. Design: A prospective study was conducted on children aged 2 to 16 years old, hospitalized for mild TBI according to the Glasgow Coma Scale between September 2009 and June 2013. Clinical parameters, basal pituitary hormone assessment at 0, 6 and 12 months, as well as a dynamic testing (insulin tolerance test) 12 months after TBI were performed. Results: The study included 109 children, the median age was 8.5 years. Patients were investigated 6 months (n=99) and 12 months (n= 96) after TBI. Somatotropic deficiency (defined by a GH peak <20mUI/l in two tests, an IGF-1 <-1SDS and a delta height <0SDS) were confirmed in 2 cases. There was one case of gonadotrophic deficiency one year after TBI among 13 pubertal children, no precocious puberty, 5 cases of low prolactin level, and no case of corticotropic insufficiency (cortisol peak <500nmol/l) nor diabetes insipidus. Conclusion: Pituitary insufficiency was present one year after mild TBI in about 7 % of children. Based on our results, we suggest to test children after mild TBI in case of clinical abnormalities. i.e for GH axis, IGF-1 should be assessed for children with a delta height <0 SDS, 6 to 12 months after TBI, and a dynamic GH testing (preferentially by an ITT) should be performed in case of IGF-1 <-1SDS, with a GH threshold at 20 mUI/L. However, if a systematic pituitary assessment is not required for mild TBI, physicians should follow children one year after mild TBI with a particular attention to growth and weight gain.